Consumption and hegemony of Japan: A case study on consumer culture of Japanese identity products toward undergraduates - Diana Puspitasari; Yudi Suryadi; Heri Widodo (Komunitas, 2023)
This research aims to find the relationship between consumer culture lifestyle and Japanese identity products with educational background. Through this research, would know the things that encourage consumer culture towards products with Japanese identity. The subject of this study were undergraduates of Jenderal Soedirman University majoring in Japanese literature survey method. This research analysis was descriptive qualitative using the perspective of the lifestyle-culture consumer-culture industry while the data is presented quantitatively. The study found that the tendency to consume Japanese-identified products was due to the impression that they were part of Japan and the belief that Japanese-style variants tasted betters. There are no undergraduates majoring in Japanese literature who consider products with Japanese identity as ordinary goods. That shows that those who have studied Japanese have indirectly been hegemonized and become agents of cultural intermediaries. Through consumption culture, they give meaning to products with a Japanese